Mother Africa's Exceptionalism? Income and Fertility Redux - Mark Gradstein; Phoebe W. Ishak (Institute of Labor Economics (IZA), 2022)
We revisit the effect of long run income growth on population fertility in some of the poorest countries in the world. Causal inference is enabled through proxying income windfalls by oil price shocks in oil rich versus oil poor provinces. Using various fertility measures as outcomes, we find that long run income growth significantly and robustly reduces fertility. Further analysis suggests that young women's fertility is particularly affected and that women's education; age of marriage, and the age of first birth, but not the use of contraceptives, are among the important mechanisms.
Keywords: I15; J13; O15; O47; 330; economic development; population fertility; Africa